SCIENTIFIC COMMUNICATIONS IN THE INFORMATION EPOCH - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the research of the influence of scientific communications systems on the process of a scientific cognition in the information epoch.